The Effect of Social Media Addiction on Premenstruel Syndrome and Sleep Quality - Yeşim Aksoy Derya; Zeliha Özşahin; Sinem Güven Santur (Genel Tıp Dergisi)
Objective: This study was conducted to determine the impact of social media addiction on premenstrual syndrome (PMS) and sleep quality. Material-Method: The study population consisted of female students enrolled in the Health Sciences Faculty of a public university (n=884). Data were collected using the "Personal Information Form," "Social Media Addiction Scale (SMAS)," "Premenstrual Syndrome Scale (PMSS)," and "Pittsburgh Sleep Quality Index (PSQI)" instruments. Descriptive statistics, Pearson correlation analysis and Linear Regression Analysis were used for statistical evaluation. Results: The mean age of the students was 20.40±1.65, and the mean age of menarche was 13.42±1.60. The mean total score for PMSS was 129.57±37.75, the mean total score for SMAS was 12.93±4.84, and the mean score for PSQI was 13.22±2.04. The correlation analysis revealed a positive relationship between SMAS and the total scores of PMSS and PSQI (r=.325, p=.000; r=271, p=.000). In addition, as a result of the regression analysis, a 1-unit change in the social media addiction scale score causes a positive increase of .325 units (β) on the total score of the premenstrual syndrome scale and a positive increase of 0.444 units (β) on the total score of the PSQI. Conclusion: Social media addiction was found to be an effective variable in increasing premenstrual syndrome symptoms and poor sleep quality.